Implementasi Peraturan Mahkamah Agung (PERMA) Nomor 1 Tahun 2016 Tentang Prosedur Mediasi di Pengadilan Agama Kota Jambi yang Efektif dan Berkeadilan - Maryati, Maryati; Mahila, Syarifa; Restarum, Triamy; Puspita, Sri Ayu Indah; Tresya, Tresya; Islah, Islah; Masriyani, Masriyani (Wajah Hukum, 2026)
This study aims to analyze the implementation of Supreme Court Regulation (PERMA) Number 1 of 2016 regarding mediation procedures at the Religious Court of Jambi City from the perspective of effectiveness and justice. The research employs a normative juridical method with statutory, conceptual, and case approaches. The findings indicate that although the substance of the PERMA is clear and the structural mechanisms are in place, the main challenges lie in legal culture and mediation practices that still need strengthening. A low level of legal culture affects the compliance of the parties involved, resulting in suboptimal mediation outcomes. This study recommends enhancing socialization, improving mediator professionalism, and strengthening legal culture to make mediation more effective and just.